Underlying assumptions in team effectiveness research: An application of problematization methodology - Nandan Prabhu; Rashmi Y. Pai; Abhishek S. Rao K. P. (Cogent Economics & Finance, 2019)
This paper examines current assumptions underlying the team effectiveness literature so as to propose alternative assumptions. Problematization methodology was used to problematize the existing assumptions. Integral Framework was applied to categorize constructs of team effectiveness literature. Alternative assumptions were proposed along with a discussion on their theory generation potential and the potential audience to whom these assumptions would be of benefit. Results of the application of problematization methodology and integral framework have problematized the three current assumptions, i.e."experienced meaningfulness", "outside-in" view of team processes, and the impact of "structure on behavior" of team members. Alternative assumptions of "felt meaningfulness", inside-out' view of team processes, and the impact of "culture of leadership on behavior" of team members have resulted in relevant research propositions. Limitations and directions for future research are discussed along with theoretical and managerial implications.
Keywords: 330; Transformational leadership; workplace spirituality; team effectiveness; team motivation